New Evidence for Strategic Differences between Static and Dynamic Search Tasks: An Individual Observer Analysis of Eye Movements - Dickinson, Christopher; Zelinsky, Gregory (Frontiers in Psychology, 2013)
Two experiments are reported that further explore the processes underlying dynamic search. In Experiment 1, observers’ oculomotor behavior was monitored while they searched for a randomly oriented T among oriented L distractors under static and dynamic viewing conditions. Despite similar search slopes, eye movements were less frequent and more spatially constrained under dynamic viewing relative to static, with misses also increasing more with target eccentricity in the dynamic condition. These patterns suggest that dynamic search involves a form of sit-and-wait strategy in which search is restricted to a small group of items surrounding fixation. To evaluate this interpretation, we developed a computational model of a sit-and-wait process hypothesized to underlie dynamic search. In Experiment 2 we tested this model by varying fixation position in the display and found that display positions optimized for a sit-and-wait strategy resulted in higher d' values relative to a less optimal location. We conclude that different strategies, and therefore underlying processes, are used to search static and dynamic displays.